ANALYSIS OF PUBLIC AND PRIVATE - SECTORS PARTNERSHIP (PPP) IN HOUSING DELIVERY IN, NIGER STATE. NIGERIA - B, Jiya Amos; I, Shaibu S; E, Jiya Moses; Abdullahi, Idris (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Abstract: One of the greatest challenge confronting both rural and urban residents in Niger State is the need to provide adequate shelter. This study examined the individual significant contribution of the public and private sector in public-private partnerships (PPP) in housing contracts in Niger State, Nigeria. The study review that PPP has so far achieved little success in providing decent and unaffordable housing accommodation to Nigerlites. Accordingly to Niger State housing corporation 2 bedrooms flat worth N3,500,000.00 and 3 bedrooms flat worth N4,500,000.00 so it’s clear that the houses are unaffordable to low and medium incomes earners. The researcher finding that the private sector in Niger State can be said to have contributed very little to the development of an urban project in the state, however, even this insignificant level of participation has been serious challenges by poor funding and lack of policy framework to regulate it activities. Therefore, it is paramount importance that the state should develop a regulatory framework and partner with the private sector in this regard so as to ensure that the resident of Niger State has access to this important component of the human environment. Researcher concluded that to ensure the effective participation of the private sector in housing delivery in Niger State in general and Minna in particular, the following recommendation has been put forward (1) Aside from providing enabling environment for the private sector to develop real estate, government should also invest more in provision of site and services scheme this will hasten the development of estate sector. (2) The establishment a power federal mortgage bank (FMB) and urban development bank would guarantee investors access to loan and other facilities needed for mass housing development.(3) strengthening the activities of the Niger State Ministry of land and housing in order to ensure that both the formal and informal neighborhood save provided with sanction and neighborhood facilities and (4) The establishment of a PPP steering committee in the Niger State that would be responsible for the general oversight of state’s PPP arrangement. (5) Finally, the study recommends that to ensure the success of public and private partnership in housing delivering, all tiers of government must strive to complement the weakness of the public sector with the strength of the private sector.